2018
DOI: 10.1002/cre2.135
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced endothelial cell responses – possible roles during periodontal disease

Abstract: Background and objective Inflammatory periodontal pockets are known to be hypoxic. Hypoxia influences vascular response to periodontal inflammation, including angiogenesis, which is critical for oxygen and nutrient delivery to periodontal tissues and granulation tissue formation. Our previous work suggests that periodontal bacteria may actively contribute to pocket hypoxia. Herein, we test the hypothesis that Fusobacterium nucleatum actively induces low oxygen tension, which modulates angiogenesis and endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Previous studies have revealed hypoxia triggered a significant cell death by mediating iNOS/Cox-2 pathway [21][22][23]. Thus, we detected the expression changes of Cox-2 and iNOS in H9c2 cells following ghrelin pre-treatment and H/R.…”
Section: Ghrelin Protects H9c2 Cells Against H/r-induced Cell Deathmentioning
confidence: 81%
“…Previous studies have revealed hypoxia triggered a significant cell death by mediating iNOS/Cox-2 pathway [21][22][23]. Thus, we detected the expression changes of Cox-2 and iNOS in H9c2 cells following ghrelin pre-treatment and H/R.…”
Section: Ghrelin Protects H9c2 Cells Against H/r-induced Cell Deathmentioning
confidence: 81%
“…During orthodontic tooth movement, pressure and tension zones develop in the periodontal ligament [ 3 ], resulting in reduced oxygen levels [ 2 ]. HIF-1α is the main transcriptional regulator during hypoxic conditions [ 10 , 11 ], regulating the transcription of hypoxia-inducible factors such as VEGF [ 24 , 25 ] or COX-2 [ 26 ]. Accordingly, we detected increased VEGF and COX-2 expression during pressure application, whereas only COX-2, not VEGF, was increased with tensile strain, which was previously shown in PDLF [ 6 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The orthodontic forces during OTM are transmitted to endothelial cells, promoting the migration of leukocytes, which secrete many signalling molecules, such as cytokines, chemokines, and growth factors, as well as inflammatory mediators that stimulate PDL and alveolar bone to remodel the ECM (Di Domenico et al., 2012; Mendes et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after force application, the bloods vessels respond with increase of permeability. In this phase, it a decrease of CD31, an adhesion molecule on endothelial cells, occurs, suggesting an increased potential for vascular permeability (Mendes et al., 2018). During orthodontic therapy, biological activity is characterized by an increase in cellular response (Baumrind, 1969; Storey, 1973).…”
Section: Introductionmentioning
confidence: 99%